EFFICIENCY OF LOGISTICS CHAIN MANAGEMENT IN THE GRAIN PRODUCT SUBCOMPLEX OF THE AGRO-INDUSTRIAL COMPLEX OF UKRAINE - Volodymyr KOLODIICHUK; Heorhiy CHEREVKO; Iryna KOLODIICHUK; Roman POPIVNIAK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The results of improving of conceptual-categorical apparatus of the study of logistics systems and effective functioning of enterprises of grain products subcomplex of Agro-Industrial Complex (AIC) by clarifying and specifying the definitions of “logistics chain” and “efficiency of management of logistic chains” are presented in this article. It is proved that in order to adapt Ukrainian logistics systems to the level of world requirements, a qualitative assessment of the effectiveness of logistics chain management should be carried out using the a highquality assessment of logistics chain management needs to be made using the World Bank's Logistics Performance Index (LPI). The results of the analysis of the impact of the relevant factors and the development of ways to activate the appropriate reserves on the management of logistics chains in the grain subcomplex are the basis for improving methodological approaches to identify opportunities to increase the efficiency of this process. The classification of factors of influence on the efficiency of functioning of logistic chains in the grain subcomplex of AIC is offered, and the division of microlevel factors into structural-organizational and functional-economic ones is substantiated. It is determined that the most characteristic factors of macro and meso level are the effectiveness of governmental regulation, the degree of involvement of the grain products subcomplex of agroindustrial complex in international logistics systems and the degree of development of the grain market infrastructure.